Sanchez-Llamas v. Oregon - Bodansky, Daniel; Bradley, Curtis A. (The American journal of international law, 2006)
Sanchez-Llamas v. Oregon, 126 S.Ct. 2669. United States Supreme Court, June 28, 2006. In Sanchez-Llamas v. Oregon, a majority of the U.S. Supreme Court held that suppression of evidence is not an appropriate remedy for violations of Article 36 of the Vienna Convention on Consular Relations and that U.S. states may apply their regular procedural default rules to bar claims brought under Article 36. The Court reached the latter conclusion despite contrary reasoning by the International Court of Justice (ICJ). Article 36(1)(b) of the Vienna Convention provides that when one party country arrests nationals of another party country, it shall inform the foreign nationals without delay that they have the right to have their consulate notified of the arrest, and to communicate with the consulate. Article 36(2) adds that these rights “shall be exercised in conformity with the laws and regulations of the receiving State, subject to the proviso, however, that the said laws and regulations must enable full effect to be given to the purposes for which the rights accorded under this Article are intended.” The United States ratified the Vienna Convention in 1969, along with a protocol to the Convention providing that disputes between nations arising under the treaty could be heard in the ICJ.